Hypersensitivity induced in dogs by nymphal extract of Amblyomma cajennense ticks (Acari : Ixodidae) - Mukai, L. S.; Netto, A. C.; Szabo, MPJ; Bechara, G. H.; Gibbs, EPJ; Bokma, B. H. (New York Acad Sciences, 2002)
In general, hosts develop resistance to ticks after repeated infestations; nevertheless, several studies on naturally occurring host-tick interactions were unable to detect resistance of hosts to ticks even after repeated infestations. The purpose of this investigation was to study the type of cutaneous hypersensitivity to unfed nymphal extract of A. cajennense in dogs, which, unlike guinea pigs, do not develop resistance. A first, but no second, peak in skin reaction was observed, suggesting that cellular immunity is an important mechanism of resistance to ticks. This may partially explain why guinea pigs, but not dogs, develop resistance against ticks.
Keywords: Amblyomma cajennense; Tick infestation; Rickettsia rickettsii